HEVC intra prediction analysis for optimization - Sulochana, V.; Shanthini, B.; B. Praveen, G. (International Journal of Engineering and Technology, 2018)
Increasing demand for video data has driven new video compression standard HEVC successor of H.264/AVC which is intended to achieve 50% gain in compression efficiency. Compared to H.264 which had only 9 intra prediction mode, more angular intra prediction mode directions are introduced in this standard. Increase in the performance proportionally increases the complexity of encoder and hence a fast method is required to choose the optimal direction. In this work, we have studied existing literatures that are envisioned to reduce intra coding time and briefly presented the comparison for future enhancement.